1999
DOI: 10.21273/horttech.9.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Flat Design for Forced-air Cooling of Blueberries Packaged in Plastic Clamshells

Abstract: Forced-air cooling rates of highbush blueberries (Vaccinium corymbosum L.) packaged in 6-oz (177-mL) or 1-pt (473-mL) clamshell containers were affected by positions of vent holes in corrugated flats. Most rapid cooling occurred in flats with vents across the top of the flat. Additional vents aligned in front of clamshells resulted in more rapid and uniform cooling than vents placed between clamshells. Vent holes in the bottom of flats had no effect on cooling rates. Clamshells cooled more slowly in the front … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…3 Previous research studies have shown that prost-harvest practices such as harvesting at correct maturity, careful handling, proper transportation are very important before storing in cold storage in order to reduce post-harvest losses of fruits and vegetables. [4][5][6][7] At present, there are lack of studies available for investigate fruits and vegetable post-harvest losses and technology gaps in Sri Lanka. Therefore, objective of this review is to investigate causes for postharvest losses of fruits and vegetables, and present status of fruits and vegetable supply chain in Sri Lanka; from farmer level to up to consumer.…”
Section: Introductionmentioning
confidence: 99%
“…3 Previous research studies have shown that prost-harvest practices such as harvesting at correct maturity, careful handling, proper transportation are very important before storing in cold storage in order to reduce post-harvest losses of fruits and vegetables. [4][5][6][7] At present, there are lack of studies available for investigate fruits and vegetable post-harvest losses and technology gaps in Sri Lanka. Therefore, objective of this review is to investigate causes for postharvest losses of fruits and vegetables, and present status of fruits and vegetable supply chain in Sri Lanka; from farmer level to up to consumer.…”
Section: Introductionmentioning
confidence: 99%